Electron backscatter diffraction study of dislocation content of a macrozone in hot-rolled Ti-6Al-4V alloy - Britton, T; Birosca, S; Preuss, M; Wilkinson, A (2010)
We compare the dislocation substructure within macrozone and non-macrozone regions of hot-rolled Ti-6Al-4 V. Hough-based and cross-correlation-based analysis of electron backscatter diffraction (EBSD) patterns are used to establish the grain orientations and intra-granular misorientations, respectively. The set of geometrically necessary dislocations (GNDs) that support measured lattice curvatures and minimize the total GND line energy are calculated. The GND content in the macrozone is approximately twice that in the non-macrozone region, and 〈a〉 GNDs are present at densities ∼10 times higher than 〈c + a〉 GNDs. © 2010 Acta Materialia Inc.